2021
DOI: 10.1108/ijtc-09-2020-0183
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral intention of traveling in the period of COVID-19: an application of the theory of planned behavior (TPB) and perceived risk

Abstract: Purpose This paper aims to examine travelers` behavioral intention of traveling in the period of coronavirus by employing the theory of planned behavior. The framework incorporates attitude, subjective norms, perceived behavioral control and a very crucial construct, i.e. perceived risk, as per the current critical scenario of COVID-19. Design/methodology/approach Data was collected using a survey instrument on the internet by posting the questionnaire link over social network web pages of online traveling w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
2
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 92 publications
6
46
2
10
Order By: Relevance
“…From the results of the study, two variables in the TPB model are Attitude andand PBC (Percieved Behavioral Control) has a positive and significant effect on the intention to travel to Sabang City in the midst of the Covid 19 pandemic, where Attitude is the variable that has the largest contribution in influencing Intention. These empirical findings are in line with the findings of other researchers using the TPB model and in the context the COVID-19 pandemic (Sandra, et al, 2020, Bae & Chang, 2020, Li, et al, 2020, Xu, et al, 2021, Pahrudin, et al, 2021, and Sujood, et al, 2021.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…From the results of the study, two variables in the TPB model are Attitude andand PBC (Percieved Behavioral Control) has a positive and significant effect on the intention to travel to Sabang City in the midst of the Covid 19 pandemic, where Attitude is the variable that has the largest contribution in influencing Intention. These empirical findings are in line with the findings of other researchers using the TPB model and in the context the COVID-19 pandemic (Sandra, et al, 2020, Bae & Chang, 2020, Li, et al, 2020, Xu, et al, 2021, Pahrudin, et al, 2021, and Sujood, et al, 2021.…”
Section: Discussionsupporting
confidence: 90%
“…Meanwhile, the results of this study indicate that the Subjective Norm has no effect on Intentions traveling to Sabang City in the midst of the Covid 19 pandemic, these findings are in accordance with (Pahrudin, et al, 2021, andSujood, et al, 2021) who confirmed that the Subjective Norm was not significant for predicting the intention to travel during the COVID-19 pandemic situation. In contrast, with the model and context of COVID-19, several other researchers found a significant influence on the Subjective Norm.…”
Section: Discussionsupporting
confidence: 84%
“…Several meta-analyses have provided evidence for the ability of the components of the TPB to predict general health behaviors (e.g., [ 15 ]). Interestingly, numerous studies have addressed these associations during the COVID-19 context, on several health behaviors such as physical distancing [ 16 ], mask wearing [ 17 ], handwashing [ 18 ], intentions of traveling [ 19 ], and intentions to receive a COVID-19 vaccine [ 20 , 21 ]. In the same vein, Prasetyo and colleagues [ 22 ] demonstrated that factors derived from an extended version of TPB were significantly associated with behavioral intention (see also [ 23 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the findings from the sample suggest that individuals are more inclined to use pro-environmental services in the future. According to Sujood and Bano (2021) , there is substantial societal pressure to abide by preventative behaviour, and if family members or peers have a biassed attitude regarding preventative measures, the probability of an individual following the same behaviour would be likely high.…”
Section: Discussionmentioning
confidence: 99%